Kesesuaian dan Kapabilitas pada Adopsi Komunikasi Pemasaran Digital Usaha Mikro, Kecil, dan Menengah di Wilayah Kulon Progo: Compatibility and Capability on the Adoption of Digital Marketing Communication for Micro, Small, and Medium Entreprises in the Kulon Progo Region - Desideria Cempaka Wijaya Murti (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
MSMEs are a crucial sector in Indonesia, yet they still face numerous challenges in their development. Therefore, countless capacity-building training programs are conducted to address various challenges in this sector. One of the primary challenges faced by MSMEs is marketing, particularly on digital platforms. This study addresses this need by evaluating MSMEs' marketing implementation capabilities in Kulon Progo Regency and the extent to which they can implement digital marketing communications in their businesses. Digital marketing communications encompass digital branding, social media management, visual and written content creation, and e-commerce platforms. To examine the various stages of development in this adoption capability, this study employed a mixed-methods approach, including an initial survey and an analysis of online data. This study examined the stages and aspects of MSME development to increase the adoption of digital marketing communications, a key issue in this sector. The findings indicate that MSMEs are striving to increase their visibility, identity, and sales activities through various media, combining these with face-to-face marketing.